The sisterhood : the 99ers and the rise of U.S. women's soccer - Goldman, Rob (University of Nebraska Press, 2021)
""The Sisterhood" is the story of the first generation of national team players, known as the 99ers, who were the driving force behind the rise of U.S. women's soccer and who built the foundation for the team's enduring success"--